The Dialectics of Rent-Seeking and Value Creation: An Economic Analysis of Constitutional Constraints in Indonesia’s Danantara - Utomo, Bagus Satrio; R Edi Sewandono; Novita Triyatun; Herry Respati Kusuma; Ince Ahmad Zarqan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The establishment of Badan Pengelola Investasi Daya Anagata Nusantara (Danantara) represents a paradigmatic shift in Indonesia’s state capitalism, consolidating state-owned enterprise assets exceeding USD 57 billion within an unprecedented super-holding governance structure. This article employs constitutional political economy and economic analysis of law to interrogate the hypothesis that institutional designs permitting high executive discretion without adequate constitutional constraints generate exponential agency costs. Through comparative institutional analysis contrasting Danantara with Temasek Holding, Khazanah Nasional, and 1MDB as a counterfactual failure, this study applies Jensen and Meckling’s (1976) agency theory, Williamson’s (1985) transaction cost economics, and North and Weingast’s (1989) credible commitment framework to evaluate the efficiency implications of presidential appointment authority. The analysis demonstrates that Danantara currently occupies a suboptimal position on the institutional possibility frontier, positioned within a rent-seeking zone characterized by high political interference risk and moderate transparency. The article argues that legal legitimacy depends upon implementing credible commitment mechanisms, specifically constitutionalized investment mandates, arm’s length director selection procedures, and minority shareholder protections, that constrain ultra vires risks while preserving operational efficiency. These findings demonstrate that without adequate institutional engineering, asset consolidation amplifies agency costs multiplicatively through cascading principal-agent relationships, potentially resulting in welfare losses exceeding 8–12 percent of assets under management.